(untitled) (ENTHYMEMA, 2024)
Being sharp and characterized by well-marked distinctive features, Lenin’s style was, for the Formalists, a crucial ground for applying their theories to the most contemporary issues. Particularly indicative in this respect is issue 1(5) of the LEF magazine, published in 1924 and devoted to Lenin’s language. It includes also an article by Boris Kazansky, a multifaceted personality, trained as a classicist; for him, the classical rhetoric and oratory, rethought from the perspective of the present, became the key to addressing Lenin’s discourse and its devices, as well as a fundamental object of dialogue with the members of OPOJaZ grappling with a necessary opening of theoretical and methodological horizons. The aim of this contribution is to present for the first time to the Italian reader the author, who is still little known, and to analyse his 1924 article, comparing it with a shorter text from 1939 on the same subject but built with a very different approach. A translation of both texts, never published before in Italian, is presented in the appendix.